Biochar enhanced phytostabilization of heavy metal contaminated mine tailings: A review - Shi, Yanfeng; Zang, Yufei; Yang, Huanhuan; Zhang, Xu; Shi, Jinmiao; Zhang, Jie; Liu, Bing (Frontiers in Environmental Science, 2022)
Mining activities has generated large amounts of mine tailings each year, and these tailings usually contain high concentrations of heavy metal pollutants, which not only cause serious damage to the local and surrounding soil ecosystems, but also harm human health via the transmission of food chain. Phytoremediation is treated as environmentally friendly, long-term effective and low-cost restoration method. However, tailing soil acidification, low organic matter content, poor water holding capacity and compaction make plant struggle to survive. Biochar, a soil conditioner can promote plant growth by improving the physical, chemical and biological properties of soil, thus strengthening the ability of phytoremediation in the contaminated tailings. This review elaborates how the physicochemical properties of biochar affect phytoremediation; and summarized how the raw materials of biochar affect the physicochemical characteristics. Finally, the future research directions are prospected.